Serum Osteocalcin as a Marker for Vitamin K-Status in Pregnant Women and Their Newborn Babies - Jie, Kon-Siong G; Hamulyák, Karly; Gijsbers, Birgit L M G; Roumen, Frans J M E; Vermeer, Cees (Thrombosis and Haemostasis, 1992)
Osteocalcin (bone Gla-protein) is a vitamin K-dependent protein synthesized by osteoblasts. Its hydroxylapatite binding capacity (HBC) is generally used to estimate the Gla-content of circulating osteocalcin. Here we have used the HBC of serum osteocalcin as a marker for the vitamin K-status in pregnant women and their offspring. For all cases investigated the HBC values in the cord samples were substantially lower than in the corresponding maternal ones. Babies from mothers who had been treated with vitamin K during the last 6 weeks prior to delivery, had significantly higher HBC values than those from a placebo group. The results presented in this paper are indicative for a generally occurring vitamin K deficiency in newborns. At delivery the HBC in untreated women was low as well. In both the placebo- and the vitamin K-group a good correlation was found between the HBC values in paired samples from mother and child. Whether the maternal HBC value may be used as a prenatal marker for estimating the fetal vitamin K-status remains to be seen.